Experimental Investigation on Al2O3 & Cu/Oil Hybrid Nano fluid using Concentric Tube Heat Exchanger. (2018) - Phanindra, Y.; Kumar, S.D.; Pugazhendhi, S.
Abstract: Now a days, Heat transfer is an important aspect in industries. Heat Exchangers are basically used for this purpose in Industries. Heat transfer using nano fluids give good results compared to normal base fluids. This report deals with an experimental study on the forced convective heat transfer and flow characteristics of a hybrid nano fluid which consists of Transformer oil and 0.1% volume concentration of Al2 O3 /Cu nano particles. Hybrid nanofluid is the mixture of two individual nanopowders in different proportions which is mixed with the base fluid in required volume concentration. The nanoparticles are synthesized separately by two step method and then dispersed in oil to form nanofluid. The properties such as thermal conductivity, density, viscosity of this nanofluid is found out. The mixture then is made to flow in a concentric tube heat exchanger in which inner tube is made of copper which has high thermal conductivity and shell side is made up of mild steel material. Al2 O3 /Cu nano particles of 60nm diameter are used in this experiment. Experimental setup is made which consists of a concentric tube heat exchanger and required mountings such as thermostats and flow meter to calibrate the values needed. Nusselt number values are calculated at each experiment with and without mixing of nanoparticles and compared. Overall heat transfer rate is compared between the normal base fluid and experiment with the usage of nanofluid in the required concentration. Obtained values are graphically plotted and the variation in heat transfer rate is presented.